Purification of beryllium by acetylacetone EDTA solvent extraction: procedure and chemistry - Bamberger, C. E. L.; McDuffie, H. F.; Baes, C. F. (1965)
Fil: Bamberger, C. E. L. Comisión Nacional de Energía Atómica; Argentina